Optimization of Phase-Change Material–Elastomer Composite and Integration in Kirigami-Inspired Voxel-Based Actuators - Decroly, Gilles; Raffoul, Romain; Deslypere, Clara; Leroy, Paul; Van Hove, Louis; Delchambre, Alain; Lambert, Pierre (Frontiers in Robotics and AI, 2021)
Phase-change material–elastomer composite (PCMEC) actuators are composed of a soft elastomer matrix embedding a phase-change fluid, typically ethanol, in microbubbles. When increasing the temperature, the phase change in each bubble induces a macroscopic expansion of the matrix. This class of actuators is promising for soft robotic applications because of their high energy density and actuation strain, and their low cost and easy manufacturing. However, several limitations must be addressed, such as the high actuation temperature and slow actuation speed. Moreover, the lack of a consistent design approach limits the possibility to build PCMEC-based soft robots able to achieve complex tasks. In this work, a new approach to manufacture PCMEC actuators with different fluid–elastomer combinations without altering the quality of the samples is proposed. The influence of the phase-change fluid and the elastomer on free elongation and bending is investigated. We demonstrate that choosing an appropriate fluid increases the actuation strain and speed, and decreases the actuation temperature compared with ethanol, allowing PCMECs to be used in close contact with the human body. Similarly, by using different elastomer materials, the actuator stiffness can be modified, and the experimental results showed that the curvature is roughly proportional to the inverse of Young’s modulus of the pure matrix. To demonstrate the potential of the optimized PCMECs, a kirigami-inspired voxel-based design approach is proposed. PCMEC cubes are molded and reinforced externally by paper. Cuts in the paper induce anisotropy into the structure. Elementary voxels deforming according to the basic kinematics (bending, torsion, elongation, compression and shear) are presented. The combination of these voxels into modular and reconfigurable structures could open new possibilities towards the design of flexible robots able to perform complex tasks.